Navigating the Future: A Review on Challenges and Innovations in Healthcare Network Technologies - Parmadi, Budi Dhaju (Devotion : Journal of Research and Community Service, 2024)
Healthcare is a vital part of a healthcare system, which is governed by a set of responsibilities and responsibilities. This paper explores the evolution of healthcare systems through the use of the Internet of Things (IoT) and telemedicine. The paper aims to identify areas for improvement and explore strategies to leverage network technologies to enhance healthcare offerings and outcomes. The data analysis technique used was thematic analysis. Thematic analysis identified and categorized key themes related to challenges and innovations in the collected studies. Telemedicine, supported by cloud computing, offers significant potential for improving healthcare delivery but faces challenges related to high assurance, interoperability, and storage adaptability. The development and use of telecommunications technology in healthcare require careful policy considerations to address the significant challenges in healthcare delivery. The research also explores how technology influences the development of healthcare delivery systems known for its efficiency, accessibility, and improved patient welfare.